2017
DOI: 10.1002/glia.23260
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐checkpoint blockade with anti‐PD1 antibodies does not alter cerebral amyloid‐β burden in several amyloid transgenic mouse models

Abstract: Chronic inflammation represents a central component in the pathogenesis of Alzheimer's disease (AD). Recent work suggests that breaking immune tolerance by Programmed cell Death-1 (PD1) checkpoint inhibition produces an IFN-γ-dependent systemic immune response, with infiltration of the brain by peripheral myeloid cells and neuropathological as well as functional improvements even in mice with advanced amyloid pathology (Baruch et al., (): Nature Medicine, 22:135-137). Immune checkpoint inhibition was therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…Previous studies showed that systemic anti-PD-1 treatment enhanced memory in mouse AD models, as a results of recruitment of immune cells (e.g., macrophages) and subsequent clearance of amyloid- plaques 3,4 . Contradictory results were also reported 5,6 . We previously demonstrated the presence of functional PD-1 in peripheral sensory neurons which regulates nociceptor excitability and pain 7 .…”
Section: Pd1-deficient Neurons Showed No Changes In Ap Amplitude and mentioning
confidence: 72%
“…Previous studies showed that systemic anti-PD-1 treatment enhanced memory in mouse AD models, as a results of recruitment of immune cells (e.g., macrophages) and subsequent clearance of amyloid- plaques 3,4 . Contradictory results were also reported 5,6 . We previously demonstrated the presence of functional PD-1 in peripheral sensory neurons which regulates nociceptor excitability and pain 7 .…”
Section: Pd1-deficient Neurons Showed No Changes In Ap Amplitude and mentioning
confidence: 72%
“…Furthermore, blockade of PD‐1 in a mouse model of Alzheimer's disease (AD) improves cognitive performance (Baruch et al, ), suggesting a broad role of NCRs in CNS pathologies. However, the effectiveness of PD‐1 blockade in AD is still not resolved (Latta‐Mahieu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of PD-1 antagonists stimulated IFN-γ T-cell responses, which facilitated the clearance of cerebral amyloid β and improvements in cognitive symptoms (Baruch et al, 2016). Conflicting studies, however, find that while PD1 engagement stimulated systemic immune activity; it did not lead to improvement in amyloid pathology or cognitive impairments (Latta-Mahieu et al, 2018). In addition, PD-1 immunotherapy in cancer patients also elicits pronounced immune activation, but patients commonly develop depression symptoms and cognitive impairments (Bower et al, 2009).…”
Section: Tlr4mentioning
confidence: 99%